Regulasi pengawasan iklan obat tradisional yang berlaku di Indonesia - Taqiyyah Qothrunnadaa; Ade Zuhrotun (Journal of Pharmaceutical and Sciences, 2023)
The economic growth of the pharmaceutical industry is in line with the growing growth of the Indonesian herbal or traditional medicine industry. People's interest in buying a product is influenced by several factors. One of them is the way the product is promoted, such as advertising. The increasing circulation of traditional medicines has led to an increase in the use of excessive advertising or unscrupulous producers who do not meet the requirements, so a system is needed that can protect the public and ensure that the advertisements promoted are in accordance with applicable regulations. Therefore, a search of primary and secondary literature related to regulations regarding Advertising was carried out. The regulation governing advertising, especially for Traditional Medicines, is Keputusan Menteri Kesehatan No. 386/MENKES/SK/IV/1994 mengenai Pedoman Periklanan: Obat Bebas, Obat Tradisional, Alat Kesehatan, Kosmetika, Perbekalan Kesehatan Rumah Tangga dan Makanan-Minuman.